A New Approach to the Interpretation of Voice Commands - Kronbauer, Artur Henrique; Costa, Vinicius Ferrari (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
The first 15 years of the twenty-first century are marked by the significant evolution of a new area known as Ubiquitous and Pervasive Computing. The introduced concepts are materializing in significant technological advances in different scenarios of humans’ daily life, especially the so-called Ambient Intelligence (AmIs). In this context, one of the relevant research points is to enable human-computer interaction to become transparent and preserve the natural shape of existing communication between humans. Thus, this work contributes to the studies in this area, with the specification of a new model for voice interaction in AmI. To validate the proposed model, an infrastructure was built, based on the specified components. The potential of infrastructure and its possible large-scale adoption are evaluated by the execution of a preliminary experiment.